TRANSFORMATION OF FAMILY VALUES IN THE PROCESS OF GLOBALIZATION (European Journal of Interdisciplinary Research and Development, 2025)
This article analyzes how the processes that occurred in the world during the 20th century have influenced the social, economic, political, and cultural landscape of the 21st century in the context of globalization and examines their consequences. Generally, the fundamental mechanism shaping today's society is directly linked to the institution of family and its associated values. The article pays particular attention to these aspects. It presents conclusions on the evaluations given to interpretations of the concepts "traditional family" and "modern family." This article is devoted to the analysis of how globalization processes in the world during the 20th century have impacted the social, economic, political, and cultural image of the 21st century and their outcomes. In general, the main mechanism shaping the image of contemporary society is directly related to the institution of family and its values. The article pays special attention to these aspects. Conclusions are presented on the assessments given to the interpretations of the concepts of "traditional family" and "modern family." This article analyzes how the processes of globalization that occurred in the world during the 20th century have influenced the social, economic, political, and cultural landscape of the 21st century and their consequences. In general, the fundamental mechanism shaping modern society is directly linked to the institution of family and its values. The article pays special attention to these aspects. It presents conclusions on the interpretation of the concepts of "traditional family" and "modern family."